2015
DOI: 10.15414/jmbfs.2015.4.special1.41-44
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Chemical Quality of Slovak and European Honey

Abstract: The aim of the present study was to evaluate microbiological and chemical quality of honey from Slovakia, Czech Republic and Germany. Selected microbiological and chemical parameters were determined in 12 samples of honey. Total Viable Count (TVC), coliform bacteria (CB), microscopic filamentous fungi (MFF) moisture content and free acids were determined. Plate dilution method with individual culture conditions was used for microorganisms cultivation. Moisture content was measured by refractometry and free aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…Journal of Food Quality good practices of harvest and conditioning of the honey, which agrees with data found by Kunová et al [7] and Iglesias et al [50].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Journal of Food Quality good practices of harvest and conditioning of the honey, which agrees with data found by Kunová et al [7] and Iglesias et al [50].…”
supporting
confidence: 91%
“…Beekeeping is the most bene ted from the wealth of Moroccan ora, with a main annual production estimate between 2500 and 3500 tons of honey [6]. e evaluation of honey quality is a crucial step to guarantee the safety of the consumers, notably to evaluate the good practice of beekeepers in order to draw up relevant strategies focused on the quality of production and standards establishing [7].…”
Section: Introductionmentioning
confidence: 99%
“…As reported Kunová et al (2015), four samples of honey from 3 different EC country were negative for microscopic fungi count. The maximum value of microscopic fungi in one sample of honey was 1.5 x 10 2 CFU.g -1 (from Slovakia).…”
Section: Honey From Buckwheatmentioning
confidence: 64%
“…Total mesophilic aerobic bacteria, total anaerobic bacteria, yeast and mold counts are important parameters used to determine the microbial quality of honey. Kunová et al (2015) reported that the total viable count ranged from 1.87 log cfu/g to 3.87 log cfu/g with a median level of 2.52 log cfu/g, based on the analysis of honey samples originating from the Czech Republic, Slovakia and Germany. Pucciarelli et al (2014) reported that the mean TMAB count of the analyzed honey in Argentina was as 3.13 log cfu/g, Rozanska and Osek (2012) reported a TMAB count ranging from 1.9x10 2 cfu/g to 4.6x10 3 cfu/g for five honey types of different botanical origin in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Honey being consumed without undergoing any prior heat treatment or preservation techniques requires strict attention to be paid to good manufacturing practices during its production. Previously reported studies from different countries have shown that retail honey can contain vegetative and spore-forming bacteria, yeast and mold (Ceauşi et al, 2009;Kačániová et al, 2012;Dümen et al, 2013;Erkan et al, 2015;Kunová et al, 2015;Moujanni et al, 2017;Combarros-Fuertes et al, 2019). Besides, most of these studies focused on determining microbiological profile rather than microbial diversity at species level from the samples.…”
Section: Introductionmentioning
confidence: 99%